Effects of chromium picolinate and ascorbic acid dietary supplementation on nitrogen and mineral excretion of laying hens reared in a low ambient temperature (7°C) - Şahin, Kazım; Şahin, Nurhan (Vysoka Skola Veterinarni Farmaceuticka, 2002)
The effects of chromium (chromium picolinate, CrPic) and ascorbic acid (L-ascorbic acid) supplementation on nitrogen (N), ash and mineral retention in laying hens (Hy-Line) reared under a low ambient temperature (7degreesC) was evaluated. One hundred and twenty laying hens (32-week-old) were divided into four groups, 30 hens per group. The laying hens were fed either a basal diet or the basal diet supplemented with either 400 mug of Cr/kg of diet, 250 mg of L-ascorbic acid/kg of diet, or 400 mug of Cr plus 250 mg of L-ascorbic acid/kg of diet. Retention of N, ash, Ca, P, Zn, Fe and Cr were highest with the combination of chromium and ascorbic acid and were lowest with the control diet (P < 0.05). Accordingly, excretion of N, ash Ca, P, Zn, Fe and Cr was lesser in chromium and ascorbic acid supplemented groups than the control (P < 0.05), that of combination of supplemental chromium and ascorbic acid being lowest. Results of the present study show that supplementing ascorbic acid and chromium, particularly as a combination, improved retention of mineral and decreased excretion of nitrogen, ash, Ca, P, Zn, Fe, and Cr in laying hens. Such a combination of supplementation can offer a potential protective management practice in preventing the detrimental effects of cold stress in laying hens. The results of the present study also show that chromium and vitamin C had additive effects on parameters measured at the present study.
Keywords: cold stress; chromium; ascorbic acid; mineral excretion; laying hen